PENGENALAN ETIKA BERBAHASA INGGRIS KELOMPOK SADAR WISATA DI DESA BONGKASA, KABUPATEN BADUNG. - I MADE RAJEG; LP. LAKSMINY; I KETUT TIKA; I NENGAH SUDIPA (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2006)
ABSTRACT This community services took place in the Village of Bongkasa-Badung regency involving 29 participants of Tourism Awareness Group (Pokdarwis) in that village. The topic of this services is about the English Ethic using the appropriate English constructions in communication with English speaking tourists. Apart from being able to use English grammatically, the participants are also introduced by the appropriate ways of using communicative English in order that they feel more confident in interacting with the tourists.